Orotransmucosal Drug Delivery: An Emerging Approach for Treating Oral Mucosa Disease - Mahmud, Hasan; Himi, Afnan Sayeid; Rifat, Md. Muhtamim Hussain; Rana, Md. Sohel; Ritika, Khyam Radhifa; Labonno, Kazi Sanjida Alam; Akter, Sunjida; Islam, Swarnali (Pharmaceutical Science: New Insights and Developments Vol. 6, 2025)
Orotransmucosal drug delivery is an alternative method used for systemic drug delivery. It is used as a favoured route for non-parenteral administration of emergency drugs and agents. This route offers both advantages and limitations, notably the rich vascularisation of oral mucosal surfaces. It can be used both for lipid-soluble and water-soluble drugs. It increases drug solubility and reduces the permeability of the lipid bilayer membrane. Mucosal surfaces are often rich in blood supply, allowing for rapid drug transport into the systemic circulation and, in most cases, avoiding degradation by first-pass hepatic metabolism. These systems contact with absorbent surfaces improve absorption at the application site and increase dwell time. It involves several physiological features of the oral cavity. Technical difficulties and biological impediments can be used as broad categories to group oral administration issues. Orotransmucosal drug delivery system still faces some difficulties, such as pH, enzymatic activity and mucosal permeability. In this study, the mechanism of oral transmucosal administration of fentanyl citrate (OTFC) was examined. Orotransmucosal drug delivery system uses an absorption rate four times that of the skin. It is easily accessible and heals rapidly from trauma and injury. It has a smaller surface area than the skin and can only be exposed for brief periods of time. Thus, this delivery method is the best for medications with high therapeutic potency. Efficient orotransmucosal drug delivery can be achieved in the oral cavity's buccal, sublingual, palatal and gingival regions. Mastication or chewing food can improve or impair medication absorption in the oral cavity. Mucoadhesive drug delivery systems can be lost or damaged when used to fill chewing gum with drugs that are released when the chewing gum is chewed, to distribute active substances quickly and conveniently via the oral mucosa. QuickStripTM was created as a fast-disintegrating thin film matrix. This report also provides input for future orotransmucosal drug developments to treat oral mucosa diseases. Researchers aim to overcome permeability barriers, protect drugs from enzymes and consistently deliver effective doses using novel methods.